DEVELOPMENT OF A DIGITAL E-CRM AS A SOLUTION FOR CUSTOMER RELATIONSHIP MANAGEMENT AND TRANSACTION ACTIVITIES AT TOKO ZUMA - Nurul Azzuma; Afdhal Syafnur; Elly Rahayu (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2026)
Abstract: Toko Zuma faces challenges in optimizing customer relationship management and transaction recording due to conventional manual systems, which hinder real-time loyalty monitoring and sales analysis. This research aims to design a digital Electronic Customer Relationship Management (E-CRM) system as an integrative solution for systematic and centralized management. The design method employs Unified Modeling Language (UML) for requirements analysis, user interface design, and Black-box Testing for validation. Results demonstrate a 100% success rate across all primary modules. The platform features Point Reward, automated transaction management, and live chat for direct interaction. Implementation enables personalized promotional strategies based on accurate data to increase customer retention. In conclusion, the Digital E-CRM system effectively automates business processes, serving as a strategic instrument for transparent and measurable customer relationship management. Keywords: digital e-crm; relationship management; toko zuma; transaction activities. Abstrak: Toko Zuma menghadapi kendala dalam optimalisasi manajemen hubungan pelanggan dan pencatatan transaksi karena masih menggunakan sistem manual konvensional. Penelitian ini bertujuan merancang sistem Electronic Customer Relationship Management (E-CRM) digital sebagai solusi integratif untuk pengelolaan basis data dan transaksi secara terpusat. Metode perancangan meliputi analisis kebutuhan menggunakan Unified Modeling Language (UML), desain antarmuka, dan validasi fungsional melalui Black-box Testing. Hasil pengujian menunjukkan tingkat keberhasilan 100% pada seluruh modul utama. Platform ini dilengkapi fitur Point Reward, manajemen transaksi otomatis, dan media interaksi live chat. Implementasi sistem ini memungkinkan strategi promosi personal berdasarkan data akurat untuk meningkatkan retensi pelanggan. Simpulannya, sistem E-CRM digital berhasil mengotomatisasi proses bisnis dan menjadi instrumen strategis dalam manajemen hubungan pelanggan yang transparan dan terukur. Kata kunci: aktivitas transaksi; digital e-crm; pengelolaan relasi; toko zuma.